2005
DOI: 10.1097/00024665-200511000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in NCLEX-RN Readiness Preparation for Baccalaureate Student Success

Abstract: Success for first-time takers of the NCLEX-RN has implications for the students, faculty, and nursing programs. As the passing standard for the NCLEX-RN has risen, some programs have experienced a corresponding decrease in their graduates' first-time pass rates. This article describes one baccalaureate program's journey from low first-time NCLEX-RN pass rates in 2001 to greater student and program success using a data-based, analytical approach. Although passing an exit exam was a program requirement for 20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…However, the presence of fluent and sympathetic English speakers with a backup local Arabic speaking GNI coordinator was important for maintaining focus on the linguistic requirements for the HAAD exam. 4.2.2 Development of critical thinking skills Focus on the nursing process and use of case studies is noted as an enabler in the development of critical thinking skills, nursing judgment, and in successful remediation and exam preparation programs (Colombraro, 1989;Frith et al, 2005;Hyland, 2012;Norton et al, 2006). Week one of the program included daily presentation and discussion of a clinical case study (Table 1).…”
Section: Program Evaluation: Thematic Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of fluent and sympathetic English speakers with a backup local Arabic speaking GNI coordinator was important for maintaining focus on the linguistic requirements for the HAAD exam. 4.2.2 Development of critical thinking skills Focus on the nursing process and use of case studies is noted as an enabler in the development of critical thinking skills, nursing judgment, and in successful remediation and exam preparation programs (Colombraro, 1989;Frith et al, 2005;Hyland, 2012;Norton et al, 2006). Week one of the program included daily presentation and discussion of a clinical case study (Table 1).…”
Section: Program Evaluation: Thematic Analysis and Discussionmentioning
confidence: 99%
“…The team found that while recommendations are available on the design and delivery of review programs and remedial interventions to assist nurses preparing for high-stakes licensing exams (Crow, Handley, Shaw-Morrison, & M., 2004;Frith, Sewel, & Clarke, 2005;Kaufman, Baradell, Calhoon, & Durham, 1987;Morton, 2004), most of the literature was focused on the NCLEX (Colombraro, 1989;Johnson, 2009;Norton et al, 2006;Pennington & Spurlock, 2010). No articles were found of direct relevance to nursing within the UAE, wider Gulf Cooperation Council (GCC) States or an Arab Muslim context.…”
Section: Exploring the Literature To Inform Program Planningmentioning
confidence: 99%
“…2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The predictive accuracy of the E2 has been studied regularly since 1999. 2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The predictive accuracy of the E2 has been studied regularly since 1999.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Background information for the course development process was described by Frith et al 4 The course has been continually modified using student feedback and exit NCLEX examination passing scores. Background information for the course development process was described by Frith et al 4 The course has been continually modified using student feedback and exit NCLEX examination passing scores.…”
Section: Implementing An Nclex Preparation Coursementioning
confidence: 99%